Utilization of Information and Communication Technology in Performance Management: For a Better Organization - I Gede Putu Kawiana (International Publisher (YAPENBI), 2023)
Rapid developments in ICT have provided new opportunities for organizations to improve operational efficiency, communication and human resource management. However, the concrete impact of ICT implementation on performance management still requires more in-depth research. This study aims to investigate how the use of Information and Communication Technology (ICT) can influence and improve performance management in an organizational context. This research will use a qualitative approach with descriptive methods. This study underscores the importance of performance management in achieving organizational goals. By linking strategic planning and tactical execution, ensuring administrative efficiency, managing human resources well, and encouraging individual development, performance management becomes an important foundation for company growth and success. The use of Information and Communication Technology (ICT) in this process strengthens effectiveness by simplifying performance reviews, providing more targeted feedback, and creating a fair and personalized environment. In today's dynamic era, the combination of strong performance management and ICT utilization provides the necessary tools for organizations to adapt, develop and achieve competitive advantage.